Patterns of Intimate Partner Violence and the Harsh Parenting of Children - Rousson, Ashley N. (Journal of interpersonal violence, 2023)
While research shows that adult intimate partner violence (IPV) and harsh parenting of children co-occur, less information is available about whether specific types or patterns of IPV create greater risk for harsh parenting, and whether these patterns vary by gender. This study used latent class analysis (LCA) to examine unique patterns of IPV perpetration and victimization among men and women, and variation across patterns by gender, parenting status, and harsh parenting of children. Data are from the Lehigh Longitudinal study (n = 332). LCA produced four classes of IPV perpetration and victimization (Minor Psychological; None; Moderate; and Severe), which were invariant by gender. Although any level of IPV was associated with an increase in harsh parenting, patterns of IPV characterized by a greater number of and more severe types, were particularly associated with the use of harsh parenting toward their children for both mothers and fathers. Parents were overrepresented in all IPV classes compared to the No-IPV class. Results suggest the need for more broad screening and increased supports for parents that are tailored to different levels of need.